Studi Perbandingan Sistem Kepegawaian Di Negara Indonesia Dan Jepang - Daulay, Syamsiyah Adilah; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
Comparing human resource management systems in the public sector is a topic discussed in comparative studies of Public Administration. This research focuses on comparing the personnel systems between Indonesia and Japan, especially in terms of recruitment, promotion and employee rotation. The method used in this research is a literature review using valid and reliable secondary data. Data was obtained from sources such as books, scientific journals, online news and official websites. The aim of this research is to expand understanding of how the civil service system is run in Indonesia and Japan, as well as to find good practices that can be adopted in the civil service system in Indonesia.